2023
DOI: 10.1007/s11846-023-00618-z
|View full text |Cite
|
Sign up to set email alerts
|

The strategic effect of corporate reputation on customer citizenship behavior: an empirical verification

Abstract: Corporate reputation (CR) can support a business from different perspectives, significantly affecting its key outcomes; however, the relationship between CR and customer citizenship behaviour (CCB) has received little consideration in research so far. The aim of this paper is therefore dual: to study the direct effect of CR on three different dimensions of CCB; and to examine the moderating effects of personality differences (extroversion and neuroticism) and gender in relation to the respective relationships.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 162 publications
(253 reference statements)
0
2
0
Order By: Relevance
“…Similarly, earlier studies found how customers participate in brand advocacy for social causes, with the individuals with inherent tendencies having a solid emotional bond with the brand and perceiving it as their identity (Delpechitre et al , 2018; Itani et al , 2022). Likewise, customers exhibiting a higher brand engagement are more inclined to showcase customer citizenship behavior (Nicola et al , 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, earlier studies found how customers participate in brand advocacy for social causes, with the individuals with inherent tendencies having a solid emotional bond with the brand and perceiving it as their identity (Delpechitre et al , 2018; Itani et al , 2022). Likewise, customers exhibiting a higher brand engagement are more inclined to showcase customer citizenship behavior (Nicola et al , 2023).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that a positive corporate reputation leads customers to positive attitudes and behaviors such as trust, loyalty, and satisfaction (De Nicola et al, 2023). In today's competitive conditions, companies have become more dependent on the positive attitudes and behaviors of customers.…”
Section: Purpose and Sample Of The Studymentioning
confidence: 99%